ACTION CURVES WITH SINGLE PEAKS IN NITELLA IN RELATION TO THE MOVEMENT OF POTASSIUM - Osterhout, W. J. V. (The Rockefeller University Press, 1940)
In Nitella the action curve has two peaks, apparently because both protoplasmic surfaces (inner and outer) are sensitive to K(+). Leaching in distilled water makes the outer surface insensitive to K(+). We may therefore expect the action curve to have only one peak. This expectation is realized. The action curve thus obtained resembles that of Chara which has an outer protoplasmic surface that is normally insensitive to K(+). The facts indicate that the movement of K(+) plays an important part in determining the shape of the action curve.